Transparansi, Hasil Audit Laporan Keuangan dan Korupsi pada Pemerintah Provinsi di Indonesia - Cinintya, Christine; Gamayuni, Rindu Rika; Dharma, Fitra (E-Jurnal Akuntansi, 2022)
Transparency and audit results on government management are important things that can be used to reduce corruption. This study aims to determine the effect of transparency, audit findings and follow-up on recommendation of audit results on corruption, using data from 28 provincial governments during 2013 – 2020. The research population is the provincial government in Indonesia, and uses Microsoft Excel and Eviews for data processing. The test results on 224 samples show that transparency has a negative effect on corruption, and audit findings have a positive effect on corruption. Meanwhile, follow-up on recommendation of audit results has no effect on corruption. Keywords: Transparency; Findings; Follow-Up; Corruption